Recent advances in microcatheter technology for the treatment of chronic total occlusions. (3rd April 2019) - Vemmou, Evangelia; Nikolakopoulos, Ilias; Xenogiannis, Iosif; Megaly, Michael; Hall, Allison; Wang, Yale; Chavez, Ivan; Garcia, Santiago; Burke, M. Nicholas; Brilakis, Emmanouil S.
ABSTRACT: Introduction : Use of a microcatheter is essential for chronic total occlusion (CTO) percutaneous coronary intervention (PCI). Several microcatheters have recently been introduced in clinical practice aiming to improve deliverability and resistance to deformation. Areas covered : We review the technical characteristics of several new microcatheters (Mamba, Mamba Flex, Teleport Control, Teleport, Nhancer Rx, Sasuke, and ReCross) and compare them with existing microcatheters. Expert opinion : The recently developed microcatheters offer additional options for guidewire support during CTO PCI. Accumulation of clinical experience and performance of comparative effectiveness studies are needed for better understanding the role of these devices in contemporary CTO PCI.